A solution framework for the multi-mode resource-constrained cross-dock scheduling problem. (March 2016) - Hermel, Dror; Hasheminia, Hamed; Adler, Nicole; Fry, Michael J.
Abstract: In this paper we propose a framework for shift-level container scheduling and resource allocation decisions at a cross-dock facility. The Multi-Mode Resource-Constrained Cross-Dock Scheduling Problem (MRCDSP) approach minimizes material flow and schedules inbound and outbound containers to dock-doors such that the total processing time is minimized subject to the resource constraints at the cross-dock. While container scheduling and resource allocation problems at cross-dock facilities have been studied previously in isolation, our work is the first to consider a complete view of cross-dock operations providing optimal container to dock-door allocation, and a makespan minimizing schedule of containers to the cross-dock. We present a comprehensive framework that includes identification of container clusters to reduce the problem size, a container-to-dock-door assignment algorithm, and a container clusters scheduling model that is solvable for practically sized problems. In a comparative numeric study based on data simulating a cross-dock facility, our approach is shown to outperform current practice, reducing the average time required for processing a set of containers by 37% and reducing the weighted-distance material traveled within the cross-dock by 45%. Abstract : Highlights: We study shift-level operations management at a cross-dock. We provide a novel framework for container scheduling and resource allocation at a cross-dock facility. We show, using a comparative study, the positive impact of our suggested framework.